Analisis Faktor Yang Memengaruhi Kualitas Hidup Lansia Penderita Hipertensi Di Wilayah Puskesmas Tangan-Tangan Kabupaten Aceh Barat Daya - Musaddik Musaddik; Asriwati Asriwati; Nur’aini Nur’aini (Journal of Educational Innovation and Public Health, 2024)
Data from the World Health Organization (WHO) estimates that currently the global prevalence of hypertension is 22% of the total world population. Based on data on hypertension in the elderly in the Tangan-Tangan Community Health Center, Southwest Aceh Regency in 2021, there were 517 people, in 2022 there were 668 people, while in 2023, starting from January-August, there were 712 people. The aim of the research is to determine the factors that influence the quality of life of elderly people with hypertension in the Tangan-Tangan Community Health Center Area, Southwest Aceh Regency. The research design uses the Analytical Survey method with a Cross Sectional approach. The population in this study were all elderly people who experienced hypertension in the Tangan-Tangan Health Center Working Area, Southwest Aceh Regency, totaling 712 people. The sample consisted of 88 people using Quota sampling technique. Data analysis uses univariate, bivariate and multivariate analysis. The results of the research show that there is an influence of physical activity, diet, medication adherence, motivation and family support on the quality of life of elderly people with hypertension in the Tangan-Tangan Health Center Area, Southwest Aceh Regency, while the dominant factor is family support. The conclusion of this research is that there is an influence of physical activity, diet, medication adherence, motivation and family support on the quality of life of elderly people with hypertension in the Tangan-Tangan Health Center Area, Southwest Aceh Regency. It is recommended that the Tangan-Tangan Health Center create a program as a forum for hypertensive patients to always carry out efforts to control blood pressure as a form of monitoring and maintaining the patient's quality of life.